2√3-4√2-(6√3-3√3+5√2)-(2√2+5√3-7√2)
Răspunsuri la întrebare
Răspuns de
5
Răspuns:
Explicație pas cu pas:
2√3-4√2-(6√3-3√3+5√2)-(2√2+5√3-7√2) =
2√3 - 4√2 - (3√3 + 5√2) - (5√3 - 5√2) =
2√3 - 4√2 - 3√3 - 5√2 - 5√3 + 5√2 =
2√3 - 3√3 - 5√3 - 4√2 =
- 6√3 - 4√2
Răspuns de
3
Răspuns:
-6√3 - 4√2
Explicație pas cu pas:
2√3 - 4√2 - ( 6√3 - 3√3 + 5√2 ) - ( 2√2 + 5√3 - 7√2 ) =
= 2√3 - 4√2 - ( 3√3 + 5√2 ) - ( -5√2 + 5√3 )
= 2√3 - 4√2 - 3√3 - 5√2 + 5√2 - 5√3 ( -5√2 cu 5√2 se reduc )
= 2√3 - 4√2 - 3√3 - 5√3
= √3( 2 - 3 - 5 ) - 4√2
= -6√3 - 4√2
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Franceza,
9 ani în urmă
Engleza,
9 ani în urmă